University Social Responsibility as Ethical Management: The UAM Model under Vallaeys’ Theory - Sandoval Suazo, Thelma del Carmen (Scientific journal of social studies, 2026)
This article analyzes the management of University Social Responsibility (USR) at the American University of Nicaragua (UAM), contrasting its institutional praxis with the Four Impacts theoretical model proposed by François Vallaeys. A qualitative single-case study approach was employed, triangulating data from documentary analysis of governing regulations (Statutes and Policies), current ISO certifications, and the foresight of the 2025-2030 Institutional Strategic Development Plan (PDEI). It is demonstrated that UAM has transcended the traditional approach of solidarity extension to adopt an auditable Impact Management system. The simultaneous integration of ISO 9001, 14001, 50001, and 21001 standards, coupled with the projection of ISO 56001 (Innovation), evidences the materialization of USR into systemic processes. USR is not a philanthropic appendix, but a transversal management policy. The UAM case exemplifies how the convergence between national accreditation and international standardization acts as a dike against institutional cosmetics, allowing the transition from legal heteronomy to ethical autonomy.